Food recall attitudes and behaviors of school foodservice directors - Grisamore, Amber A. (Kansas State University, 2013)
The purpose of this study was to explore United States school foodservice directors’ attitudes about food recalls and to determine recall practices in school foodservice operations. An online survey was used for data collection and consisted of three sections: attitudes, self-reported behaviors, and demographics. Content validity of the instrument was measured by three experts who examined the survey prior to pilot testing. The survey was pilot tested with 14 school foodservice directors and state agency personnel. Statistical analysis was completed using SPSS (v. 20.0). Internal consistency of the attitude scale was measured using Cronbach’s Alpha. All scales had a reliability coefficient greater than 0.70. The survey was randomly distributed to 4,049 school foodservice directors across the U.S. A total of 690 school foodservice directors (17%) completed the survey, with 567 being usable. Respondents rated attitudes on a 5-point scale, strongly disagree (1) to strongly agree (5). Principle components factor analysis was used to identify two factors: perceived importance and perceived likelihood of possessing a recalled product. Perceived importance was rated very high (M=4.8, SD=0.5), while perceived likelihood of possessing a recalled product was rated much lower (M=1.7, SD=0.8). Self-reported behaviors were evaluated on a 5-point scale, never (1) to very often (5). Overall, respondents reported positive behaviors related to responding to a recall. When dividing behaviors into three factors, behaviors regarding communication with state agency and vendors about food recalls (M=4.1, SD=0.6), use of recall systems (M=3.6, SD=1.0), and practices of responding to a recall (M=4.7, SD=0.4) were frequently reported. Multiple regression analysis was used to explore relationships between attitudes and behaviors of school foodservice directors towards food recalls, and their demographic characteristics. Predictors of attitudes were found to be certification, work experience, and prior experience with a food recall. Predictors of behaviors were found to be perceived likelihood of possessing a recalled product, educational level, prior experience with a food recall, and size of district. Federal and state agency personnel can use the results of this study in developing programs to improve food recall practices as well as school foodservice directors for improving recall practices in schools.
Keywords: Food recalls; Food safety; School foodservice; Food safety attitudes; Home Economics (0386); Management (0454)